Kontribusi Digital Marketing dalam Efektifitas Strategi Pemasaran Pendidikan - Ikhsan Mubarok; Liqo’ Mursidah; Ainur Rofiq (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the contribution of digital marketing to the effectiveness of educational marketing strategies at Darul Qur'an Islamic Boarding School. The study uses a qualitative approach with a case study design. Data collection techniques include semi-structured interviews, participant observation, and documentation studies involving the head of public relations, social media administrators, registration staff, and prospective guardians of students. Data analysis was conducted through thematic analysis with the stages of coding, categorization, and drawing main themes. Data validity was strengthened through source and method triangulation, member checking, audit trails, and thick description presentation. The results showed that digital marketing was able to expand the reach of pesantren promotion, accelerate the decision-making process of prospective guardians, increase trust through two-way interaction, strengthen the professional image of the institution, and improve the efficiency of the registration administration. The contribution of this study lies in strengthening the empirical evidence of the role of digital marketing as an educational marketing strategy for pesantren that is adaptive to technological transformations and the needs of modern society. Keywords: digital marketing, Islamic boarding schools, educational marketing, trust, guardians